The role of digestive system diseases in cerebrovascular disease: a comprehensive Mendelian randomization study - Qin, Hao; Suo, Shihuan; Yang, Fan; Hao, Pengfei; Zhang, Xianfeng (Frontiers in Neurology, 2024)
Background: Cerebrovascular disease, among the most prevalent neurological disorders, poses a substantial threat to human health with its elevated mortality and disability rates, placing considerable strain on healthcare systems. Although several studies in recent years have suggested a potential association between digestive system diseases and cerebrovascular diseases, the findings remain inconsistent.Methods: Genome-wide association study (GWAS) summary data for 12 digestive diseases and cerebrovascular diseases were used to conduct Mendelian randomization (MR) analysis. In this investigation, we endeavored to elucidate the causal relationship between digestive system diseases and cerebrovascular diseases.Employing a comprehensive approach, including two-sample MR (TSMR), multivariate MR (MVMR), and two-step MR analysis, we leveraged summary statistics data obtained from published GWAS. The primary analysis method employed was inverse variance weighted (IVW), with MR-Egger and weighted median (WM) as secondary methods. Sensitivity analysis included heterogeneity testing, horizontal multivariate testing, MR-PRESSO, and a "leave-one-out" method.Additionally, the F-statistic was utilized to assess the strength of instrumental variables, ensuring robust results.In the TSMR analysis, this study found a significant causal relationship between genetically predicted gastroesophageal reflux disease (GERD) and any stroke (AS), any ischemic stroke (AIS), large-artery atherosclerotic stroke (LAS), intracranial aneurysm (IA), and subarachnoid hemorrhage (SAH). In MVMR analysis, this study found that even after adjusting for systolic blood pressure (SBP), body mass index (BMI) and type 2 diabetes (T2D), the causal relationship remains exist. In the two-step MR mediation analysis, it was found that BMI, SBP and T2D play mediating role in the causal relationship between GERD and cerebrovascular diseases.This study indicates a clear positive causal relationship between GERD and cerebrovascular diseases, and this causal association remains significant even after adjusting for BMI, SBP and T2D. The mediation MR analysis suggests that BMI, SBP and T2D may mediate the causal relationship between GERD and the risk of cerebrovascular diseases.